Analysis of Management Strategies in Improving Islamic Religious Education Learning at The Tadika of The Clerk of Cheers - Azzahra, Sobrina; Pohan, Selamat (Journal of English Language and Education, 2025)
This study examines strategic management in enhancing Islamic Religious Education (PAI) learning at Cendikiawan Ceria Kindergarten, focusing on planning, implementation, and evaluation. Using a descriptive qualitative approach with interviews, observations, and document studies conducted over 25 days (August 5–30, 2024), findings show that religious programs such as iqro' reading, memorizing short surahs, daily prayers, and worship practices effectively enhance student religiosity. Strategic management involves systematic steps: formulating strategies, implementing activities, and periodic evaluations, including memorization and worship assessments. Despite its effectiveness, challenges remain, such as limited learning spaces, misaligned teacher qualifications, and student discipline management. This study highlights the need for a more conducive learning environment and professional teacher development to enhance PAI learning quality. Effective strategic management is expected to foster innovation and improve Islamic education quality at the kindergarten level.